Multicriteria decision‐making approach based on gray linguistic weighted Bonferroni mean operator - Tian, Zhang‐Peng; Wang, Jing; Wang, Jian‐Qiang; Chen, Xiao‐Hong (International transactions in operational research, 2018)
The main purpose of this paper is to provide a multicriteria decision‐making (MCDM) approach that applies the gray linguistic Bonferroni mean (BM) operator to address the situations where the criterion values take the form of gray linguistic numbers (GLNs) and the criterion weights are known. First, the related operations and comparison method for GLNs are provided. Subsequently, a BM operator and weighted BM operator of GLNs are developed. Then, based on the gray linguistic weighted BM operator, an MCDM approach is proposed. Finally, an illustrative example is given and a comparison analysis is conducted between the proposed approach and other existing methods to demonstrate the effectiveness and feasibility of the developed approach.